Identification of Dysbetalipoproteinemia by an Enhanced Sampson-NIH Equation for Very Low-Density Lipoprotein-Cholesterol - Sampson, Maureen; Wolska, Anna; Meeusen, Jeff W.; Donato, Leslie J.; Jaffe, Allan S.; Remaley, Alan T. (Frontiers in Genetics, 2022)
Dysbetalipoproteinemia (Hyperlipoproteinemia type III, HLP3) is a genetic disorder that results in the accumulation of cholesterol on highly atherogenic remnants particles.Traditionally, the diagnosis of HLP3 depended upon lipoprotein gel electrophoresis or density gradient ultracentrifugation. Because these two methods are not performed by most clinical laboratories, we describe here two new equations for estimating the cholesterol content of VLDL (VLDL-C), which can then be used for the diagnosis of HLP3. Using results from the beta-quantification (BQ) reference method on a large cohort of dyslipidemic patients (N=24,713), we identified 115 patients with HLP3 based on having a VLDL-C to plasma TG ratio greater than 0.3 and plasma TG between 150 and 1000 mg/dL. Next, we developed two new methods for identifying HLP3 and compared them to the BQ and a previously described dual lipid apoB ratio method. The first method uses results from the standard lipid panel and the Sampson-NIH Equation 1 for estimating VLDL-C (S-VLDL-C), which is then divided by plasma TG to calculate the VLDL-C/TG ratio. The second method is similar, but the Sampson-NIH Equation 1 is modified or enhanced (eS-VLDL-C) by including apoB as an independent variable for predicting VLDL-C. At a cut-point of 0.194, the first method showed a modest ability for identifying HLP3 (sensitivity=73.9%; specificity=82.6%, Area Under the Curve (AUC)=0.8685) but was comparable to the existing dual lipid apoB ratio method.The second method based on eS-VLDL-C showed a much better sensitivity (96.5%) and specificity (94.5%) at a cut-point of 0.209. It also had an excellent AUC score of 0.9912 and was superior to the two other methods in test classification. In summary, we describe two new methods for the diagnosis of HLP3. The first one just utilizes the results of the standard lipid panel and the Sampson-NIH Equation 1 for estimating VLDL-C and can potentially be used as a screening test. The second method (eS-VLDL-C), in which the Sampson-NIH Equation 1 is modified to include apoB, is nearly as accurate as the BQ reference method.Because apoB is widely available at most clinical laboratories, the second method should improve both the accessibility and the accuracy of HLP3 diagnosis.